Electrophysiological estimation of the actions of acetylcholinesterase inhibitors on acetylcholine receptor and cholinesterase in physically isolated Aplysia neurones. - Oyama, Y. (1989)
1. The actions of representative cholinesterase inhibitors on the acetylcholine responses of physically isolated single neurones from the pedal ganglion of Aplysia californica were studied, using electrophysiological techniques and rapid agonist application to analyse both the inhibitory actions on the acetylcholine receptor-channel complex and the degree of inhibition of acetylcholinesterase activity on the same neurone. The inhibitors used were physostigmine, edrophonium and diisopropylfluorophosphate (DFP). 2. When selected neurones were suddenly exposed to 50 microM acetylcholine by a 'concentration clamp' technique a large Na-dependent inward current was initiated, and decayed in the continued presence of acetylcholine without external perfusion. However, if perfusion of the acetylcholine solution was reinitiated the current increased somewhat, indicating that the decay of current was due to some combination of receptor desensitization and local depletion of acetylcholine at the membrane by acetylcholinesterase. 3. With simultaneous application of acetylcholine (50 microM) and physostigmine (0.1 to 100 microM) there was a dose-dependent reduction of peak amplitude of the acetylcholine response. However, physostigmine at low concentrations (0.1 to 10 microM) caused a time-dependent increase in the current amplitude alone with a time- and dose-dependent inhibition of acetylcholinesterase activity. At the highest concentration of physostigmine (100 microM) acetylcholinesterase activity was abolished but the current peak was very depressed. After removal of physostigmine from the bathing solution, the current amplitude decreased toward the control at the two lower concentrations as the inhibitory actions on acetylcholinesterase activity were almost reversible, while at the two higher concentrations (10 and 100 microM) the current increased and the inhibition of acethylcholinesterase remained. 4. When acetylcholine (50 microM) and edrophonium (0.1 to 10 microM) were applied simultaneously, edrophonium caused a dose-dependent increase in the peak amplitude that was correlated with a dose-dependent inhibition of acetylcholinesterase activity. Prolonged exposure to edrophonium did not change the peak amplitude and there was no time-dependent change in the inhibition of acetylcholinesterase activity. At the highest concentration of edrophonium used (100 microM), simultaneous application with acetylcholine augmented the peak amplitude relative to control, but to a lesser extent than 10 microM. Prolonged exposure to the highest concentration of edrophonium caused a time-dependent reduction in the peak amplitude.(ABSTRACT TRUNCATED AT 400 WORDS)